Study of Annular Roller Design for High Speed Traction Drive - 钱立新; 陆君毅; 吴荣仁; 汪希萱 (Jixie chuandong)
Using annular rollers as planets is an ideal design of high speed planetary traction drive.In this paper,the deformations and stresses of the roller at assemblage and operation are solved,and the method of adopting hollowness as main parameter of the roller design is presented.Also,the hollowness selection region is studied.